Contrasting Responses to Stress Displayed by Tobacco Overexpressing an Algal Plastid Terminal Oxidase in the Chloroplast - Ahmad, Niaz; Khan, Muhammad Omar; Islam, Ejazul; Wei, Zheng-Yi; McAusland, Lorna; Lawson, Tracy; Johnson, Giles N.; Nixon, Peter J. (Frontiers in Plant Science, 2020)
The plastid terminal oxidase (PTOX) – an interfacial diiron carboxylate protein found in the thylakoid membranes of chloroplasts – oxidizes plastoquinol and reduces molecular oxygen to water. It is believed to play a physiologically important role in the response of some plant species to light and salt (NaCl) stress by diverting excess electrons to oxygen thereby protecting photosystem II (PSII) from photodamage. PTOX is therefore a candidate for engineering stress tolerance in crop plants. Previously, we used chloroplast transformation technology to over express PTOX1 from the green alga Chlamydomonas reinhardtii in tobacco (generating line Nt-PTOX-OE). Contrary to expectation, growth of Nt-PTOX-OE plants was more sensitive to light stress. Here we have examined in detail the effects of PTOX1 on photosynthesis in Nt-PTOX-OE tobacco plants grown at two different light intensities. Under ‘low light’ (50 μmol photons m–2 s–1) conditions, Nt-PTOX-OE and WT plants showed similar photosynthetic activities. In contrast, under ‘high light’ (125 μmol photons m–2 s–1) conditions, Nt-PTOX-OE showed less PSII activity than WT while photosystem I (PSI) activity was unaffected. Nt-PTOX-OE grown under high light also failed to increase the chlorophyll a/b ratio and the maximum rate of CO2 assimilation compared to low-light grown plants, suggesting a defect in acclimation. In contrast, Nt-PTOX-OE plants showed much better germination, root length, and shoot biomass accumulation than WT when exposed to high levels of NaCl and showed better recovery and less chlorophyll bleaching after NaCl stress when grown hydroponically. Overall, our results strengthen the link between PTOX and the resistance of plants to salt stress.